Aconselhamento pastoral e homossexualidade: a dimensão da fé cristã nas angústias da homossecualidade - Meira, Rosana Orlandi (2012)
The present work starts with the historical positioning of Christian Religion about homosexuality, further, in a synthetic way, it expatiates about the evolution of the approach of homosexuality in medicine and psychology. In this same chapter are studied the themes of an imposition of prejudice and homophobic. The work reports to the Christian religion as a whole, not referring to any Church in particular, even when documents of some Christian church in particular. Are used in the second chapter, it seeks to conceptualize the homosexuality by the understanding of the sexuality, as one of the structures of the body that cannot be denied, but integrated to it. This chapter also approaches the question of the distress that can arise in people who are not in the heterosexual standard. In the third chapter, new ways of biblical interpretation and new theologies that seek to demystify homosexuality in religious environments are presented. This chapter seeks to question the understandings that are already crystallized in Christian churches in face of new interpretations, and to take the reader to a more mature reflection. The goal of this chapter is to filter and to bring up elements presented in other chapters that can encourage the reception of the homosexual into his/her community of faith, on the attempt that the strengthening of his/her faith can generate hope, decrease anguish and improve self-esteem. This chapter was named Search for fresh air in the hope that the Holy Spirit blast, as in Pentecost over those that follow Jesus into the reception and pastoral counseling towards homosexuals.